Development of Parigeuing-based encyclopedia as a teaching material to enhance students’ leadership attitudes - Sofiani, Yulia; Fachrurozi, Miftahul Habib; Armiyati, Laely (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
Leadership attitudes based on local value are competencies that are urgently needed. However, until now the teaching materials used by history lecturers in Universities at East Priangan still do not accommodate this. This study aims to develop an encyclopedia based on the Sundanese local leadership concept of Parigeuing as teaching material for  prospective history teachers. This research uses the research and development (R&D) method follows the ten systematic steps of the Borg & Gall model. The design of the developed encyclopedia is an excellent category of validators of teaching materials and content.  Based on the results of the limited trial, a total score of 393 was obtained which was categorized as good and in the extensive trial a score of 768 was obtained which was categorized as excellent. The effectiveness of the teaching material on leadership attitude was proven through an Independent Sample T-test on the N-Gain scores of the experimental and control classes, with results indicating t_count=13.137>t_table=2.009 and Sig. (2-tailed) = 0.000 < 0.05. The implication of this research is the need for a variety of teaching materials used by history education lecturers at the University level that accommodate the concept of local leadership. This is very important to prepare prospective history teachers students as agents of change to face various challanges in globalization era.